Impact of Texture on Sesquioxide Distribution in Southeastern Nigerian Soils - Uzoho, Bethel; Okoli, Nnaemeka; Ekwugha, Ugochi (International Journal of Environment, 2019)
Sesquioxides which play significant roles in soil classification and dominant soil properties vary in soils with particle size fractions. Using randomized complete block design, this study was conducted in the month of June 2018 to evaluate the impact of texture on sesquioxide distribution in humid rainforest soils of Southeastern Nigeria. Four mini-pedons were dug at four landscape positions (upslope, midslope, downslope and flat surface) and triplicate soil samples taken from 0-20, 20-40 and 40-60 cm depths, summing to total of 36 samples. Crystalline and amorphous Al, Fe, Mn and Si oxides were then determined at a depth of 0-20 cm using Dithionate Citrate Bicarbonate (DCB) and ammonium oxalate reagents. Dithionate and oxalate fractions in bulk soil ranged between 9300-11,400 (Fed), 390-1580 (Feox), 4600-6700 (Ald), 660-890 (Alox), 3300-5600 (Mnd), 350-580 (Mnox) and 9600-13,500 (Sid) and 1690-1790 mg kg-1 (Siox), with dithionate superior indicating high crystallinity and low mobility of the sesquioxides. Ratios of bulk soil oxalate/dithionate fractions were low and ranged between 0.04-0.17 (Feox/Fed), 0.11-0.15 (Alox/Ald), 0.10-0.16(Mnox/Mnd) and 0.13-0.18 (Siox/Sid) and confirming their crystallinity. Low Feox/Fed ratios signified that soils were well drained (< 0.35), old (< 0.65) and highly weathered (< 0.50) with the order being a decreasing sequence of upslope > flat surface > down slope > midslope. Sesquioxide contents and reactivity in soil particle size fractions (sand, silt and clay) varied with landscapes. Regression models indicated that particle size fractions accounted for 50% of 2/3rd of the bulk soil sesquioxide concentrations and that averaged over landscapes, sand fraction was more enriched with various sesquioxides than the other soil particle size fractions. Correlations between most bulk soil sesquioxide fractions and sesquioxide fractions with selected soil properties (sand, silt, clay, moisture content, total porosity, organic matter, pH, Ca and ECEC) were significant (P < 0.05).